Digitalization of Human Resource Management Systems in Enhancing Organizational Effectiveness - Murniadi (ProBisnis : Jurnal Manajemen, 2026)
The digitalization of human resource management (HRM) systems is an important strategy for organizations to enhance work effectiveness and competitiveness in the era of digital transformation. The application of digital technology in HRM includes recruitment processes, competency development, performance appraisal, and integrated employee data management based on information systems. This study aims to analyze the role of HRM system digitalization in improving organizational effectiveness. The research method employs a qualitative approach through a literature review and analysis of digital-based HRM system implementation practices in various organizations. The findings indicate that the digitalization of HRM enhances operational efficiency, data accuracy, process transparency, and the speed of managerial decision-making. Furthermore, digital systems support improved employee performance through more objective and continuous performance monitoring. Therefore, the digitalization of HRM systems contributes significantly to the overall enhancement of organizational effectiveness.